Knowledge Management System pada PT. TASPEN KCU Bandung - Anggun Pratiwi; Leonardi Paris Hansugian (ULTIMA InfoSys, 2018)
Knowledge management system (KMS) is one of many ways to foster a culture of knowledge sharing to improve quality of human resources in an organization by improving communication among employees and capturing knowledge. PT. TASPEN KCU Bandung is one company that is aware of the importance of a documentation of the data and information for the sustainability activities of the company. Currently documenting existing knowledge about human resources in PT. TASPEN KCU Bandung is unstructured so that has impacted the service activities that was not effective. Based on the analysis, there is a lot of important knowledge whose function at division of human resouces is to support the service activities for the employees of company. The method in this research is designed using Object Orientd Programming (OOP) with Unified Modeling Language (UML) tools, and using prototype system. For the result of this developt system is an application that using SECI model for can be used in accordance with the needs of PT. TASPEN KCU Bandung. With the construction of this KMS, employees and division of human resources can share information and knowledege whenever and wherever. Keywords : human resources, knowledge management system, knowledge